Effect of Scaffold of Bioactive Glass in the Treatment of Periodontal Bony Defects. A Prospective Clinical Study - Mukherjee, Sayan; Srivastava, Amit Kumar; Mishra, Sunil Kumar; Kundu, Debabrata (Journal of Nepalese Prosthodontic Society, 2026)
Introduction: Bioactive glass seems to promote osteogenesis and helps in rapid bone formation. The purpose of the present study was to evaluate clinical and radiographical effect of scaffold of bioactive glass in the treatment of different forms of periodontal bony defects. Methods: Total 44 different types of periodontal bony defects site were selected from total 15 patients for the study. A split mouth technique was used to compare the test sites and control sites. In each patient, the test site was treated with both bioglass scaffold and GTR membrane. Control site was treated with GTR membrane alone. The patients were grouped as: Group A: intrabony periodontal defects (n= 24 defects); Group B: suprabony periodontal defects (n= 10 defects); Group C: furcation involvement (n=10 teeth with grade II furcation). Parmeter’s evaluated were gingival index (GI), plaque index (PI), probing pocket depth (PPD), relative attachment level (RAL) and radiological bone height (RBH) at baseline and 6-month post operative. Intergroup comparison was done using independent t test and intragroup comparison was done using dependent t test. Results: There was no statistically significant improvement in the GI and PI scores from baseline to 6 months following surgery in three groups. When three groups compared together, there was a significant reduction of 3.07 mm PPD at test sites and 1.79 mm at control sites. When three groups compared together, test sites showed a reduction of 3.16 mm of RAL at test sites and 2.61 mm at control sites. Six months postoperative follow up results showed a statistically significant bone fill in case of intrabony defects and furcation defects but statistically insignificant bone fill was noticed in case of suprabony defects. When RBH of two groups (Group A and Group B) compared together, the test site showed a mean radiological defect fill of 3.04 mm at test site and 2.42 mm at control site, but difference was insignificant. Conclusion: Within the limitations of this study, six months postoperative follow up results showed significant bone fill in case of intrabony defects and furcation defects, but it was insignificant in case of suprabony defects. There was no significant improvement in GI and PI scores during follow-up. PPD and RAL showed better improvement in test sites compared to control sites. The scaffold of bioactive glass showed better results in periodontal bony defects in test sites compared to control sites.